2021
DOI: 10.1101/2021.08.09.455604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific tuning of modular muscle activation patterns for locomotion in young and older adults

Abstract: There is increasing evidence that including sex as a biological variable is of crucial importance to promote rigorous, repeatable and reproducible science. In spite of this, the body of literature that accounts for the sex of participants in human locomotion studies is small and often produces controversial results. Here, we investigated the modular organization of muscle activation patterns for human locomotion using the concept of muscle synergies with a double purpose: i) uncover possible sex-specific chara… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…Further analysis is needed when subjects are divided into sub-groups to evaluate whether these factors may influence the results. According to two recent studies [ 75 , 76 ], assessing the influence of sex and age on locomotion muscle synergies, it was reported that muscle control structures are shared between sexes. However, the study revealed the existence of small but defined sex-specific differences in the way humans control locomotion and that these strategies are not entirely maintained in older age.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis is needed when subjects are divided into sub-groups to evaluate whether these factors may influence the results. According to two recent studies [ 75 , 76 ], assessing the influence of sex and age on locomotion muscle synergies, it was reported that muscle control structures are shared between sexes. However, the study revealed the existence of small but defined sex-specific differences in the way humans control locomotion and that these strategies are not entirely maintained in older age.…”
Section: Discussionmentioning
confidence: 99%
“…As these studies only considered a small number of muscles, further analysis of the inter-muscular coordination in running was limited. However, in a recent study conducted in 60 females and 60 males [59], the concept of muscle synergies could be used based on the electromyographic recording of 13 lower limb muscles at running speeds ranging from 7.2 to 13.7 km h −1 . This study found sparse sex-specific modulations of the relative muscle contribution in running.…”
Section: Running Kinematics and Muscle Electromyographic Activitymentioning
confidence: 99%
“…Although there is no direct neurophysiological evidence, our findings support these speculations. However, several limitations should be considered in the current study: first, only male participants were included in this study, and we suggest that female participants could be included in the future to further investigate the effects of CGs on muscle synergies, as well as differences between genders (Macchi et al, 2022;Santuz et al, 2022). Second, despite the patch electrodes were used to minimise extraneous pressure on the muscle belly, the application of electrode on the inside of CG still caused a slight elevation in pressure and a non-uniform pressure distribution, which is another limitation of this study.…”
Section: Discussionmentioning
confidence: 99%